2019
DOI: 10.1001/jamapediatrics.2018.3820
|View full text |Cite
|
Sign up to set email alerts
|

Natural Progression of Symptom Change and Recovery From Concussion in a Pediatric Population

Abstract: ; for the Pediatric Emergency Research Canada (PERC) Concussion Team IMPORTANCE The natural progression of symptom change and recovery remains poorly defined in children after concussion. OBJECTIVES To describe the natural progression of symptom change by age group (5-7, 8-12, and 13-18 years) and sex, as well as to develop centile curves to inform families about children after injury recovery. DESIGN, SETTING, AND PARTICIPANTS Planned secondary analysis of a prospective multicenter cohort study (Predicting Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
120
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 56 publications
14
120
1
1
Order By: Relevance
“…Although grey matter and intra-regional connectivity values did not indicate gender-specific associations, the negative association between inter-regional FC and sleep disturbances was driven by females. This association, along with the fact that females reported higher levels of sleep-related symptoms compared to males, is in line with the suggestion that concussed females are more sensitive to sleep difficulties and have protracted recovery patterns 8,51 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although grey matter and intra-regional connectivity values did not indicate gender-specific associations, the negative association between inter-regional FC and sleep disturbances was driven by females. This association, along with the fact that females reported higher levels of sleep-related symptoms compared to males, is in line with the suggestion that concussed females are more sensitive to sleep difficulties and have protracted recovery patterns 8,51 .…”
Section: Discussionsupporting
confidence: 87%
“…Predicting the recovery trajectory of a child with PPCS is encumbered by the high interindividual variability in symptoms, age, gender, and pre-morbid characteristics 8 . Our findings showed that the inter-individual variability of PPCS recovery in children is linked to variations in brain indices that are indexed by relatively simple clinical scores of sleep disturbance and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, adolescents are more likely to report symptoms for longer periods of time after their concussion than adults (Purcell, Harvey, & Seabrook, 2016). Most adults recover within 10-14 days compared to adolescents who take an average of 1 month to recover (Henry, Elbin, Collins, Marchetti, & Kontos, 2016;Ledoux et al, 2019). In addition to an extended recovery period, the management of their concussion symptoms is somewhat different.…”
Section: What Does This Article Add?mentioning
confidence: 99%